2020
DOI: 10.1016/j.actamat.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Defect behavior and radiation tolerance of MAB phases (MoAlB and Fe2AlB2) with comparison to MAX phases

Abstract: MAB phases are a new class of layered ternary materials that have already shown a number of outstanding properties. Here, we investigate defect evolution and radiation tolerance of two MAB phases, MoAlB and Fe2AlB2, using a combination of experimental characterization and firstprinciples calculations. We find that Fe2AlB2 is more tolerant to radiation-induced amorphization than MoAlB, both at 150 °C and at 300 °C. The results can be explained by the fact that the Mo Frenkel pair is unstable in MoAlB and as a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…For the 750 °C irradiated sample, the changes in the hardness and Young's modulus are much smaller than those for the RT irradiated sample, which confirms that the Ti 3 SiC 2 has better tolerance for irradiation induced mechanical properties change at 750 °C than that at RT, although changes of ~8-10% in mechanical properties observed at 750 °C are not insignificant. Modulus/GPa and at 750°C from [11][12][13][14][15][16][17][18][19][20] are shown in Figs. 6a and 6b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the 750 °C irradiated sample, the changes in the hardness and Young's modulus are much smaller than those for the RT irradiated sample, which confirms that the Ti 3 SiC 2 has better tolerance for irradiation induced mechanical properties change at 750 °C than that at RT, although changes of ~8-10% in mechanical properties observed at 750 °C are not insignificant. Modulus/GPa and at 750°C from [11][12][13][14][15][16][17][18][19][20] are shown in Figs. 6a and 6b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, under ion irradiation, Ti 3 SiC 2 was found to remain crystalline even at a very high dose of 116.9 displacements per atom (dpa) [11]. Furthermore, experiments have shown that at temperatures above 400 °C, Ti 3 SiC 2 has a better resistance to radiation-induced cracking as compared with other MAX phase materials, such as Ti 3 AlC 2 and Ti 2 AlC [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MoAlB, as the most studied MAB phase, has been widely investigated from theoretical simulations [3][4][5] to experimental studies, and exhibits attractive mechanical properties, high temperature properties, radiation tolerance, and ablation resistance [6][7][8][9][10][11][12]. So far, MoAlB as the only one in the MAB phase family has been demonstrated with better oxidation resistance than other Al-containing MAB phases (such as Fe 2 AlB 2 and Cr 2 AlB 2 ) at temperatures below 1300 ℃ due to J Adv Ceram 2022, 11(2): 0-0 www.springer.com/journal/40145 the formation of a dense and continuous α-Al 2 O 3 layer [13][14][15][16].…”
Section: Introduction mentioning
confidence: 99%
“…Inspired by the unique properties of the MAX phases, a family of nano laminated ternary borides, named MAB phases (where M is a transition metal, A is a IIIA or IVA group element, and B is boron) were proposed by Ade and Hillebrecht [4] in 2015. MAB phases are anticipated to exhibit similar properties to the MAX phases, such as good electrical conductivity, damage tolerance [5,6], resistance to thermal shock [7] and oxidation [8] at high temperatures, as well as superior high-temperature strength [7] and self-healing capability of cracks [9].…”
Section: Introduction mentioning
confidence: 99%